BS9 Regional alterations to the transverse-tubule network in an ovine model of myocardial infarction. (4th June 2021) - Perera, Tharushi; Pinali, Christian; Radcliffe, Emma; Niort, Barbara; Pius, Charlene; Trafford, Andrew
Abstract : The highly organised transverse tubule (t-tubule) network consisting of invaginations of the cell sarcolemma facilitates synchronous cardiac myocyte contraction. This study aimed to investigate post-myocardial infarction (MI) t-tubule remodelling in infarct border and remote regions in a translationally relevant ischaemia reperfusion injury MI model. Six adult sheep were used in this study (n=3 MI, n=3 control). Eight weeks after MI, left ventricular tissue was collected from the remote and border MI regions and from control sheep, processed and imaged using 3D scanning electron microscopy. The t-tubule network was manually segmented using 3dmod. One-way ANOVA with Tukey's post-hoc correction, unpaired t-tests or Mann-Whitney U test were used where appropriate. Marked disorganisation of the t-tubule network was observed in the border region following MI. Quantitative analysis revealed that in comparison to the control sheep myocardium, the MI border zone had a decreased t-tubule count (0.07 ± 0.007 tubules per μm3 in control vs 0.05 ± 0.004 tubules per μm3 in border; p = 0.02) and showed t-tubule dilation (405 ± 22 nm in control vs 533 ± 30 nm in border; p = 0.02). Whilst there was minimal disorganisation and loss of t-tubules in the MI remote region, we observed increased t-tubule length as a fraction of the cell diameter (0.41 ± 0.04 in control vs 0.56 ± 0.04 in remote; p = 0.045). In addition to gross t-tubule remodelling, we also noted post-MI fragmentation of t-tubules, particularly in the border region. In comparison to control, the number of t-tubule fragments per μm3 was increased in the post MI heart (control, 0.17 ± 0.1 fragments per μm3; border, 2.21 ± 0.7 fragments per μm3; remote, 1.20 ± 0.4 fragments per μm3; p = 0.04 border vs control; p = 0.02 remote vs control). The volume occupied by fragments as a percentage of the cell volume was also higher following MI (control, 0.003 ± 0.002 %; border, 0.071 ± 0.023 %; remote 0.014 ± 0.005 %; p = 0.003 border vs control; p = 0.013 border vs remote). Whilst there was no difference in fragments density between the remote and border regions, there was an increase in the volume of cell occupied by fragments in the MI border region compared to remote. This is explained by a larger average fragment volume in the border region (0.04 ± 0.006 μm3 in border vs 0.01 ± 0.002 μm3 in remote; p < 0.001). Our research shows remodelling of the t-tubule network in the post-MI sheep myocardium. We noted reduced t-tubule count, t-tubule fragmentation, and dilation of remaining t-tubules. Importantly our work shows that these changes occur in a regional manner, being most pronounced in the border region. These changes may reflect regional wall stresses post-MI, and we speculate that our observations may result in region-specific changes to systolic calcium and contractility post-MI. Conflict of Interest: Authors declare that there is no conflict of interest.